Lung injury and inflammation response by chronic intermittent hypoxia in rats. Issue 1 (December 2017) - Lu, Huan; Wu, Xiaodan; Fu, Cuiping; Zhou, Jing; Li, Shanqun
Abstract Background Chronic intermittent hypoxia is the primary pathophsiological feature of obstructive sleep apnea/hypopnea syndrome. The characteristics of CIH can be imitated by animal experiment models thus to study CIH related systemic organ injuries, including respiratory systems. Methods Sixteen male SD rats were randomly divided into two groups: CIH group (n = 8) and control group (n = 8). The CIH group was exposed to intermittent hypoxia circumstance for 5 weeks (8 h/day) and control group was placed in the same animal chamber exposed to normal air circumstance. Between the two groups, the inflammatory factors of IL-6 and TNF-α within serum and BALF were measured by ELISA; the structure and ultrastructure of lungs were evaluated by HE staining and electronmicroscopy. The nuclear factor-κB (NF-κB) in lung tissue was detected by Western blot. Results The concentration of IL-6 and TNF-α in serum in CIH group increased significantly (138.63 ± 43.82 vs. 41.82 ± 5.24 pg/ml and 126.62 ± 34.81 vs. 73.43 ± 5.72 pg/ml, bothP < 0.05). The concentration of IL-6 and TNF-α in BALF in CIH group was higher than that in control group (67.1 ± 24.2 pg/ml vs 39.8 ± 21.5 pg/ml and 36.61 ± 19.17 pg/ml vs 20.31 ± 8.44 pg/ml, respectively, P < 0.05). In the HE staining of lung tissue, results showed that severe inflammatory cell infiltration in alveolar walls and alveolar spaces was found in CIH group and the histological score of CIH group is higher significantly (6.857 ± 0.553 vs. 2.286 ± 0.286 g, P < 0.05); In the electronmicroscopy of TypeIIalveolar cells, results showed that karyotheca and endoplasmic reticulum were damaged obviously in Type II alveolar cells. The NF-κB increased significantly in the CIH group compared with control group (0.43 ± 0.1 vs 0.22 ± 0.05, P < 0.05). Conclusions Animal experiment model can be used to imitate the pathophysiologic changes of CIH. There are systematic and local airway inflammation coexisting in CIH rats. CIH leads to inflammatory cell infiltration and organelle damages within lung tissues. We speculated that there was some correlation between inflammation and lung damages in CIH rats.